Experimental study of tungsten impurity formation and dynamics at plasma gun facility MK-200 under condition relevant to transient events in ITER - Poznyak, I.M.; Arkhipov, N.I.; Karelov, S.V.; Safronov, V.M.; Toporkov, D.A. (Вопросы атомной науки и техники, 2012)
Tungsten targets were irradiated by intense plasma streams at plasma gun facility MK-200UG. The targets were tested by plasma loads relevant to Edge Localised Modes (ELM) and mitigated disruptions in ITER. Primary attention has been focused on investigation of impurity formation due to tungsten evaporation and on investigation of impurity transport along the magnetic field lines. Мишени из вольфрама были подвергнуты воздействию интенсивных потоков плазмы на плазменном ускорителе МК-200UG. Испытания проводились при плазменных нагрузках, характерных для ELM’ов и ослабленных срывов в ITER. Исследованы процессы формирования примесей вольфрама за счет испарения материала мишени и их распространения вдоль силовых линий магнитного поля. Мішені з вольфраму були піддані впливу інтенсивних потоків плазми на плазмовому прискорювачі МК- 200UG. Випробування проводилися при плазмових навантаженнях, характерних для ELM’ів і послаблених зривів в ITER. Досліджено процеси формування домішок вольфраму за рахунок випаровування матеріалу мішені і їх поширення уздовж силових ліній магнітного поля.